Bis‐arylidene Oxindoles as Anti‐Breast‐Cancer Agents Acting via the Estrogen Receptor. Issue 4 (31st January 2014) - Pal, Abhishek; Ganguly, Anirban; Ghosh, Avijit; Yousuf, Md; Rathore, Bhowmira; Banerjee, Rajkumar; Adhikari, Susanta
Abstract We report a new family of bis‐arylidene oxindole derivatives that show highly selective estrogen receptor (ER)‐mediated anticancer activity at low‐nanomolar concentrations in ER‐positive (ER+) breast cancer cells. In terms of cell growth inhibition, IC50 values for these compounds in ER+ breast cancer cells are two to three orders of magnitude lower than in ER‐negative (ER−) breast cancer cells and non‐cancer cells. In comparison with known bis‐arylidene drugs, these compounds are at least three orders of magnitude more toxic than tamoxifen and 1.5–4‐fold more toxic than 4‐hydroxytamoxifen in ER+ MCF‐7 cancer cells. These oxindoles inhibit ER transactivation, and their anticancer activities are inhibited in ER‐depleted MCF‐7 cells. Some of these nonsteroidal molecules also exhibit essential properties of selective ER down‐regulation. From the development of two series of bis‐arylidene oxindole‐based compounds, we report a new series of anticancer agents for estrogen‐responsive breast cancer.